Islam and Local Tradition: A Comparative Perspective of Java and Sulawesi - Ali, Muhammad (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This article examines the dynamic relationship between Islam and local tradition in Indonesia with special reference to Java and Sulawesi. Based on historical and anthropological sources, the article seeks to understand variety of interpretation and application of Islam among local Muslims within their particular context. With this aim, the article tries to examines the intricate process of religious change as world religion interacts with local forces. The article argues that since the “localization” of Islam was continuing nature in the expansion of Islam beyond the Arab homeland, the same development in Southeast Asia can be expected. By focusing on the frameworks of ‘practical Islam’ rather than ‘normative Islam’ and both accommodation and conflict between shari’ah and adat as a whole system, rather than as separate entities, the article found a common feature of Islam as it is interpreted and applied by local Muslims in Java and Sulawesi. In this two region, Islam became the dominant force but did not completely obliterate the indigenous beliefs and practices. Despite this common feature, Javanese people have been more diverse than Sulawesi people in terms of religious spectrum particularly due to the fact that animism, Hindu-Buddhism, and Islam have been incorporated into Javanese cultural system.